Critical Analysis of The Policy of Mediation Time in The Employment Disputes Settlement - Ilham Aji Pangestu; Fitri Fitri (Faculty of Law, Musamus University, 2022)
Relationship among stakeholders in an industrial environment does not always run well. The conflicts within an industrial relationship are common, and they are known as industrial relation disputes. However, the disputes must be settled such as by mediation. This study aimed to analyze and investigate the 30 (thirty) day mediation period specified by Article 15 of the PPHI Law for the settlement of industrial relation disputes by the mediator. This study is a normative legal study utilizing a statutory approach and a case approach in which legal materials were gained through literature review. It was found that the settlement period must be completed by the mediator was ideally considering two aspects: the number of cases and the number of mediators. The researchers suggested that the provisions of Article 15 of the PPHI Law cannot be implemented equally; due to each region have the different number of cases and the number of mediators. In addition, the non-ideal number of functional mediators was taking into account the aspect of the number of cases received, so currently the service and technical implementation of the settlements do not run optimally. Based on the results of the study, the researcher suggests the stakeholders: first, to revise Article 15 of the PPHI Law, which is related to the period of time for the mediator in completing the duties. Second, to increase the number of functional mediators by considering the number of cases received.